A Technical Review on the Conventional Analytical Techniques for Optimal Load Flow Investigation on Distribution Feeder Systems Network - Nworah, Kelechi; Abi, Eyo; Ekanem, Imoh (Optimality, 2025)
This technical review provides a comprehensive overview of conventional analytical techniques employed for Optimal Load Flow (OLF) investigation in distribution feeder systems. OLF is crucial for efficient power network operation, especially given the unique challenges of radial or weakly meshed distribution networks, distributed generation (DG), and dynamic load profiles. The review details the methodologies, advantages, and limitations of four key conventional methods: Newton-Raphson, Fast Decoupled Load Flow and Gauss-Seidel. While Newton-Raphson offers accuracy and fast convergence, its computational intensity can be a drawback for large systems. The Fast Decoupled Load Flow provides a quicker alternative with potential accuracy trade-offs. The Gauss-Seidel method is simple but suffers from slow and unreliable convergence. The Backward/Forward Sweep method is highlighted as particularly efficient and robust for radial distribution systems due to its non-matrix inversion approach. The study also investigates critical challenges in distribution OLF, voltage regulation, DG integration, load variability, feeder reconfiguration, and loss minimization. The conclusion emphasizes that while these conventional methods form a foundational basis, future advancements often involve their integration with advanced optimization algorithms and uncertainty management techniques to address the increasing complexities of modern smart grids.